2022
DOI: 10.3389/fonc.2022.947710
|View full text |Cite
|
Sign up to set email alerts
|

An immediate postoperative response to therapy assessment can help avoid unnecessary RAI therapy

Abstract: BackgroundRadioiodine (RAI) therapy plays a vital role in the postoperative treatment of differentiated thyroid cancer (DTC) patients underwent total thyroidectomy (TT). However, even in the presence of capsular invasion and lymph node metastasis prognosis can be excellent and a postoperative RAI treatment might not be necessary for all patients. Therefore, this study explored the criteria for avoiding unnecessary RAI therapy in these patients.MethodWe applied response to therapy assessment immediately after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, some studies revealed no signi cant difference in disease-speci c survival and recurrence-free survival in PTC patients with high-risk features between the lobectomy and total thyroidectomy groups (7,8). In addition, PTC patients with high-risk features may not require 131 I treatment after an appropriate treatment (9,10). All this may lead to considering a less aggressive treatment for PTC patients with high-risk features.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies revealed no signi cant difference in disease-speci c survival and recurrence-free survival in PTC patients with high-risk features between the lobectomy and total thyroidectomy groups (7,8). In addition, PTC patients with high-risk features may not require 131 I treatment after an appropriate treatment (9,10). All this may lead to considering a less aggressive treatment for PTC patients with high-risk features.…”
Section: Introductionmentioning
confidence: 99%